Politics of Law in Supervising Digital Disinformation During Democratic Elections in Indonesia - Satrio Adi Warsito; Bambang Slamet Riyadi; Riza Zulfikar (SEAN Institute, 2026)
This research examines the politics of law concerning the supervision of digital disinformation in democratic elections in Indonesia amid the rapid development of digital communication technology and social media platforms. The study aims to analyse the effectiveness of Indonesia’s legal framework in supervising digital political communication during elections and to identify the reconstruction of legal policy necessary to maintain electoral integrity and democratic legitimacy. The spread of fake news, political propaganda, algorithmic manipulation, and artificial intelligence-generated political content has significantly influenced democratic participation and electoral processes in Indonesia. However, existing electoral and electronic information regulations remain fragmented and relatively reactive toward technological developments. This research employs normative legal research using statutory, conceptual, and comparative approaches. The statutory approach analyses regulations concerning elections and electronic information, while the conceptual approach examines theories of politics of law, democracy, and digital governance. The comparative approach compares Indonesia’s legal framework with several democratic countries regarding digital election supervision. The research specification is analytical-descriptive, with data collected through library research involving primary, secondary, and tertiary legal materials. Data analysis is conducted through qualitative juridical analysis based on constitutional principles and democratic values. The results show that Indonesia’s politics of law concerning digital election supervision requires adaptive legal reform through strengthening legal substance, institutional coordination, digital platform accountability, and public digital literacy. The novelty of this research lies in its analysis of digital election supervision from the perspective of politics of law by emphasizing adaptive democratic legal governance that balances freedom of expression with the protection of electoral integrity in the digital era.